Polyphenolic Composition and Allelopathic Potential of Senna cearensis Afr. Fern. (Fabaceae) (Research, Society and Development, 2020)
Chemical compounds from the secondary metabolism of a plant, termed as allelochemicals, may interfere with the germination and/or development of other plant species, a phenomenon known as allelopathy. The aim of this study was to analyze the allelopathic potential of the Senna cearensis Afr. Fern. aqueous extract at various concentrations, collected from an area in the Chapada do Araripe during two different seasons (dry and rainy), on Lactuca sativa L. and Cenchrus echinatus L. seeds and seedlings, in addition to analysing the extract’s phytochemical prospection. The bioassays were conducted in a germination chamber at 25 °C with a 12h photoperiod and consisted of four treatments (extract at 12.5%, 25%, 50% and 100%) and a control group (distilled water). The variables analyzed were: seed germination, germination speed index, radicle length and caulicle seedling length. The means from each variable were submitted to an analysis of variance and compared using Tukey’s test (p